Effects of vitamin D on vascular function and oxidative stress in the microcirculation of diabetics - Lee, Wee Chee (2020)
Diabetes mellitus contributes to macro- and microvascular complications, leading to adverse cardiovascular events. Vitamin D deficiency is associated with the development of diabetes-related cardiovascular complications. This study was divided into two parts: (i) animal study and (ii) human study. This animal study aims to determine the effects of vitamin D deficiency on (a) microvascular endothelial and smooth muscle functions in normal and diabetic rats; (b) the changes to endothelial nitric oxide synthase (eNOS) protein expression and oxidative stress parameters in mesenteric arterial tissue of normal and diabetic rats; (c) to study whether oral calcitriol supplementation is able to ameliorate microvascular dysfunction in vitamin D-deficient rats. This human study aims to evaluate the effects of vitamin D deficiency on oxidative stress status in subcutaneous arteries of diabetic patients. Animal study: (a) Male Sprague-Dawley (SD) rats were subdivided into three equal groups of 10 rats each: (i) rats receiving 10-weeks of normal diet (Group NC), (ii) rats receiving 10- weeks of vitamin D-deficient diet (Group ND) and (iii) rats receiving 10-weeks of vitamin D-deficient diet with four weeks of oral calcitriol supplementation, starting from week 7 (Groups NDS). (b) Streptozotocin-induced diabetic male SD rats were subdivided into three equal groups of 10 rats each: (i) diabetic rats receiving 10-weeks of normal diet (Group DC), (ii) diabetic rats receiving 10-weeks of vitamin D-deficient diet (Group DD) and (iii) diabetic rats receiving 10-weeks of vitamin D-deficient diet with four weeks of oral calcitriol supplementation, starting from week 7 of diabetes induction (Groups DDS). At the end of 10 weeks, all rats were sacrificed. Rats’ mesenteric arteries were isolated and dissected to undergo vascular function studies using wire myograph. Protein expression of eNOS in mesenteric arterial tissue was determined using Western blot. Immunohistochemistry was used to detect the presence and localization of eNOS in mesenteric arteries. Superoxide dismutase (SOD) and malondialdehyde (MDA) levels in mesenteric arterial tissue; fasting blood glucose (FBG), serum 25(OH)D and calcium levels in blood were also measured. Human study: Diabetic patients were categorised into two groups based on serum 25(OH)D levels: (i) vitamin D non-deficient diabetic patients (Group DNP, n = 10) and (ii) vitamin D-deficient diabetic patients (Group DDP, n = 13). The levels of SOD and MDA in subcutaneous arterial tissue were measured. Results of animal study: (a) Normal rats. Endothelium-dependent relaxation to acetylcholine (ACh) was significantly attenuated in mesenteric arteries of vitamin D-deficient rats. Reduced SOD levels and protein expression of eNOS were observed in vitamin D-deficient rats. However, calcitriol supplementation showed no significant improvement in these parameters. Endothelium-dependent contraction to calcium ionophore (CaI) was augmented in vitamin D-deficient rats receiving calcitriol supplementation. Increased calcium levels were also found in calcitriol-supplemented vitamin D-deficient rats. (b) Diabetic rats. ACh-induced endothelium-dependent relaxation was significantly impaired in mesenteric arteries of vitamin D-deficient diabetic rats. Reduced SOD levels and protein expression of eNOS and enhanced MDA levels were found in vitamin D-deficient diabetic rats. These impairments were successfully ameliorated by calcitriol supplementation. Augmented CaI-induced endothelium-dependent contraction and impaired sodium nitroprusside (SNP)-induced endotheliumindependent relaxation occurred in vitamin D-deficient diabetic rats. However, calcitriol supplementation failed to show improvement in these vascular responses There were no significant differences in endothelium-independent relaxation to salbutamol (SB) and contraction to phenylephrine (PE) as well as in general parameters such as body weight changes and FBG levels between study groups in both normal and diabetic rats. Results of human study: Markedly augmented MDA levels were found in subcutaneous arterial tissues of vitamin D-deficient diabetic patients. However, SOD levels in vitamin D-deficient diabetic patients showed the reduced trend (p = 0.072) compared to vitamin D non-deficient diabetic patients. In conclusion, this study demonstrated that vitamin D deficiency attenuates microvascular endothelial function in both normal and diabetic rats. The impairment for endothelial function was likely due to the diminished nitric oxide contribution, associated with reduced eNOS protein expression and augmented oxidative stress. Vitamin D deficiency in diabetic rats also impairs vascular smooth muscle function. The study also showed that calcitriol supplementation to diabetic rats with vitamin D deficiency improves endothelium-mediated vasodilation, by upregulating eNOS expression and improving oxidative stress status. However, calcitriol supplementation to normal rats with vitamin D deficiency induces hypercalcaemia, leading to augmented endothelium-dependent contraction. Besides that, vitamin D deficiency in diabetic patients as well showed augmented oxidative stress.